2′-O-Methylation of the second transcribed nucleotide within the mRNA 5′ cap impacts the protein production level in a cell-specific manner and contributes to RNA immune evasion. Issue 16 (26th August 2022) - Drazkowska, Karolina; Tomecki, Rafal; Warminski, Marcin; Baran, Natalia; Cysewski, Dominik; Depaix, Anaïs; Kasprzyk, Renata; Kowalska, Joanna; Jemielity, Jacek; Sikorski, Pawel J
Abstract: In mammals, m 7 G-adjacent nucleotides undergo extensive modifications. Ribose of the first or first and second transcribed nucleotides can be subjected to 2′- O -methylation to form cap1 or cap2, respectively. When the first transcribed nucleotide is 2′- O -methylated adenosine, it can be additionally modified to N 6, 2′- O -dimethyladenosine (m 6 Am ). Recently, the crucial role of cap1 in distinguishing between 'self' and 'non-self' in mammalian cells during viral infection was revealed. Here, we attempted to understand the impact of cap methylations on RNA-related processes. Therefore, we synthesized tetranucleotide cap analogues and used them for RNA capping during in vitro transcription. Using this tool, we found that 2′- O -methylation of the second transcribed nucleotide within the mRNA 5′ cap influences protein production levels in a cell-specific manner. This modification can strongly hamper protein biosynthesis or have no influence on protein production levels, depending on the cell line. Interestingly, 2′- O -methylation of the second transcribed nucleotide and the presence of m 6 Am as the first transcribed nucleotide serve as determinants that define transcripts as 'self' and contribute to transcript escape from the host innate immune response. Additionally, cap methylation status does not influence transcript affinity towards translation initiation factor eIF4E or in vitro susceptibility to decapping by DCP2; however, we observe the resistance of cap2-RNA to DXO (decapping exoribonuclease)-mediated decapping and degradation.